Electric fish barrier for protecting small carps in Eğirdir lake - Talat Yalçınkaya; Abdülkadir Çakır; Yıldız Bolat; Rahmi Uysal; Ali Aslantas (Tehnički Vjesnik, 2017)
Juvenile fishes which have economic value in Eğirdir Lake, the fourth largest lake in Turkey according to its size, are killed due to electric water pumps used for the purpose of irrigation and drinking water. In this study, an electric fish barrier was designed to keep fish away from withdrawal points of electric water pumps. Results were tested in laboratory conditions. Each experiment was performed in triplicate using 30 fish (that is, the total number of fish used for each experiment was 90). Analysis of variance (ANOVA) was used to evaluate the results by using SPSS program. The experimental results demonstrated that the 50 V/10 Hz value cannot be used because of the adverse effects. 20 V/10 Hz and 35 V/10 Hz values are suitable to keep fish away from the barriers.